Observational Evidence of Subsurface Chlorophyll Response to Mesoscale Eddies in the North Pacific - Jie Huang; Fanghua Xu (Geophysical Research Letters)
Abstract Ocean eddies were widely reported to strongly impact near‐surface chlorophyll (CHL), but most of previous studies are confined to the ocean surface. Based on large‐scale historical cruise observations with ocean mesoscale eddies detected by altimeters in the North Pacific, we show that the depth‐integrated nitrate and chlorophyll anomalies in the euphotic layer of eddies are less than ±90% for nitrate and ±10% for chlorophyll. These eddy‐driven variations decline from ocean boundaries to the open ocean, due to a combination effect of eddy activity and subsurface nitrate distribution. In the oligotrophic Pacific, CHL anomalies in both cyclonic eddies and anticyclonic eddies negatively correlate with near sea surface temperature anomalies. In contrast, an opposite correlation occurs beneath the subsurface chlorophyll maximum layer (SCML). The integrated CHL results and CHL variability at each sampling depth suggest that the vertical displacement of SCML plays an important role in the near‐surface CHL response to eddies.